INDICATOR ANALYSIS OF EMPLOYEE PERFORMANCE BASED ON THE EFFECT OF DIGITAL LEADERSHIP, DIGITAL CULTURE, ORGANIZATIONAL LEARNING, AND INNOVATION (CASE STUDY OF PT. TELKOM DIGITAL AND NEXT BUSINESS DEPARTMENT) - Muniroh Muniroh; Hamidah Hamidah; Thamrin Abdullah (STTAL POSTGRADUATE - INTERNATIONAL CONFERENCE, 2021)
The development of digital technology and the rapid transformation of information companies require skilled and innovative workers in the telecommunications industry, so companies must plan for the development of quality human resources to prepare for the era of free competition as an era of digital change. This study aims to analyze the indicators of aspects of Digital Leadership, Digital Culture, Organizational Learning, and Innovation on Employee Performance at PT. Telkom Digital Next Business Department. This study uses a quantitative approach method with the Partial Least Square (PLS) technique with one of the alternative methods of Structural Equation Modeling (SEM). The research sample is employees at the company PT. Telkom Digital and Next Business Department. Empirically the research results show that Digital Leadership does not directly affect employee performance, digital culture does not directly affect employee performance, organizational learning does not directly affect employee performance, innovation has a direct positive effect on employee performance. The results of this study imply that PT. Telkom Digital and Next Business Department need to develop Digital Leadership, Digital Culture, Organizational Learning, and Innovation in improving employee performance of PT. Telkom Digital and Next Business Department. Keyword: Employee Performance, Digital Leadership, Digital Culture, Organizational Learning